OPTIMASI KUAT TEKAN PASTA GEOPOLIMER BERBAHAN DASAR FLY ASH DENGAN VARIASI RASIO MASSA FLY ASH DAN ALKALI AKTIVATOR (FA/AA) - Nayobi, Budi; Rosidawani; Brata Adhitya, Bimo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Cement production generates high CO₂ emissions, which have a negative impact on the environment. To reduce this carbon footprint, alternative materials to cement are needed. Geopolymer paste presents a promising solution as it utilizes industrial waste such as fly ash, is environmentally friendly, and can achieve good mechanical strength. This study aims to optimize the compressive strength of fly ash-based geopolymer paste by varying the mass ratio of fly ash to alkaline activator (FA/AA). The fly ash used was characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscope (SEM) to determine its crystal structure, chemical composition, and particle morphology. The characterization results indicate that the fly ash is predominantly amorphous, classified as Class F according to ASTM C618-2019, and has spherical particles with sizes less than 2 µm, making it suitable as a geopolymer precursor. Test specimens were prepared in the form of 50 mm × 50 mm × 50 mm cubes, and compressive strength tests were conducted at 3, 7, and 28 days with varying FA/AA ratios. The test results showed that compressive strength increased with the FA/AA ratio up to an optimum ratio of 2.5, then decreased at a ratio of 3. This indicates that the FA/AA ratio significantly affects the development of compressive strength in geopolymer paste. These findings are expected to serve as a foundation for developing environmentally friendly alternative materials to replace Portland cement.